Tracing the history of shia in indonesia: History, perceptions, and contemporary challenges - Suhendri; Kamal Yusuf; Hilmadani Situmorang (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2024)
The existence of Shia as part of the treasury of Indonesian Islam is often marginalized in the mainstream narrative of history and religion, even though it has strong historical roots since the 7th to 9th centuries AD through trade and preaching routes, especially in the coastal areas of Sumatera and Aceh. In its development, the Shia community has experienced various dynamics, ranging from cultural acceptance to theological and social marginalization, especially after the reformation which was marked by increasing conservatism and identity politics. This study aims to explore the historical traces of Shia in Indonesia, examine public perceptions of it, and identify contemporary challenges faced. The research method used is qualitative based on literature studies with a descriptive-analytical approach to historical literature, relevant journals, official documents, and media reports. The results of the study show that negative perceptions of Shia are shaped by sectarian narratives, narrow religious education, and unbalanced media, which have an impact on social discrimination. Meanwhile, contemporary challenges include socio-political pressure, hate speech, and restrictions on religious freedom. Although various advocacy efforts and inter-school dialogue have been carried out, acceptance of Shia is still limited. Therefore, it is necessary to reconstruct more inclusive perceptions and policies to support a just and pluralistic religious life in Indonesia.